Computing and Combinatorics: 27th International Conference, COCOON 2021, Tainan, Taiwan, October 24-26, 2021, Proceedings - International Computing and Combinatorics Conference; Chen, Chi-Yeh; Hon, Wing-Kai; Hung, Ling-Ju; Lee, Chia-Wei (Lecture Notes in Computer Science, 2021)
This book constitutes the proceedings of the 27th International Conference on Computing and Combinatorics, COCOON 2021, held in Tainan, Taiwan, in October 2021.Due to the COVID-19 pandemic, COCOON 2021 was organized as a hybrid conference. The 56 papers presented in this volume were carefully reviewed and selected from 131 submissions. The papers are divided into the following topical sub-headings: algorithms, approximation algorithms, automata, computational geometry, fault tolerant computing and fault diagnosis, graph algorithms, graph theory and applications, network and algorithms, online algorithm and stream algorithms, parameterized complexity and algorithms, and recreational games.